HUBUNGAN DUKUNGAN KELUARGA DENGAN HARGA DIRI REMAJA PENDERITA THALASEMIA DI POLIKLINIK THALASEMIA RSUD CIAMIS TAHUN 2018 - leni mulyani; yuyun rahayu; asep gunawan (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2019)
Background : Thalassemia is a congenital blood disorder disease characterized by red blood cell (eritrosit) condition is easily damaged or shorter than normal blood cells in general. Major thalassemia affects the physical, psychological and social conditions in adolescents. Family support affects the health of thalassemia patients with a positive impact in avoiding the negative effects of severe stress.Objective : This study aims to determine the relationship of family support with the pride of adolescents thalassemia patients in polyclinic thalasemia RSUD Ciamis year 2018. Research Methodology : The type of this research is correlational quantitative research with cross sectional study design on 45 respondents. Population number 117 peoples, and sampling using totalsampling method (taken sampling) taken from adolescent thalasemia patient in polyclinic thalasemia RSUD Ciamis year 2018Research Result : Good family support with high self esteem of 2 respondents (28.6%), moderate self-esteem of 2 respondents (28.6%), and low self-esteem of 3 respondents (42.9%), For the category of family support enough with high self esteem as much as 1 respondent (2,6%), moderate self-esteem of 14 respondents (36.8%), and low self-esteem of 23respondents (60.5%).Conclusions and suggestions : There is a relationship between family support and self esteem of adolescent thalassemia patients with values (? = 0.041 at ? = 0.05). The results of this study can be used as input for hospital institutions in providing facilities and infrastructure that is privacy specific for patients with thalassemia in order to provide comfort in the treatment.